Desenvolvimento de materiais carbonáceos a partir de subprodutos do processamento de butiá (Butia spp.) e aplicação como adsorventes de fenol e CO2 - Nunes, Isaac dos Santos (2023)
Waste generation and environmental pollution contention are challenges to modern society. Liquid effluents pollute water sources and gaseous can aggravate the greenhouse effect. Adsorption highlights among the technologies that can be employed to gases and liquid treatments. In addition, biomass wastes can be employed for that, contributing for reducing solid waste generation. This work aimed to use by-products of butiá processing for adsorbents production (biochars and activated carbons) by pyrolytic route for CO2 and phenol adsorption. Biochars were produced in a reactor at 700ºC, for 1 h, using fibers, endocarps, almonds and deoiled almonds. Activated carbons were produced from fibers, endocarps and deoiled butiá almond using design of experiments, assessing different zinc chloride (ZnCl2) ratios (0.5, 1.5 and 2.5) and temperatures (400, 550 e 700°C). Endocarps presented higher yield for solid fraction at biochar and activated carbons preparations, by the higher percentage of lignin. The use of ZnCl2 at activated carbon preparation resulted in surface area increases until 2062% and formation of a structure with higher micropore volume. The higher adsorption capacity for CO2 was obtained with the biochar produced with endocarps, that reached 66.43 mg g-¹ , more effective that the higher result obtained with activated carbons (66.00 mg g-¹ for fibers with 0.5 ZnCl2 ratio, at 400ºC). Results shown that for CO2 adsorption, during 5 cycles evaluated, the biochars obtained from butiá by-products were more effective than activated carbons. Phenol adsorption with biochars presented the best result for deoiled almonds (17.69 mg g-¹ ). For activated carbons, the best result was obtained with endocarps at 700ºC and ZnCl2 ratio of 0.5, that presented 40.38 mg g-¹ , increasing in 403.49% adsorption capacity compared to respective biochar. For phenol adsorption, modification with ZnCl2 presents improvements on process effectiveness. Using decision trees on the evaluation of results obtained at production of activated carbons has clarified the importance of micropore volume percentage e micropore volume for gaseous adsorption, while for liquid adsorption pointed relevance of micropore volume and pore diameter to the best results.